Blockchain-based Learning Credential Revision and Revocation Method - San, Aye Mi; Chotikakamthorn, Nopporn; Sathitwiriyawong, Chanboon (My University, 2020)
Many blockchain-based learning credential systems have been proposed to reduce fraud and improve verification efficiency. In addition to a method for issuing and verifying credentials, a solution is needed to support the revision and revocation of an issued credential record. For the case of learning credentials, depending on how a revocation policy affects credential use that occurred before the revocation date, an additional mechanism may be needed for credential revision. Current digital learning credential methods offer only a revocation mechanism. So they do not fully meet such unique requirement in the education context. In this paper, a blockchain-based method for learning credential revision and revocation is proposed. It makes use of the revision and revocation addresses assigned to each batch of issuing credentials. To revise (revoke) one or more credentials, the proposed method stores the revision (revocation) list as a message in the OP_RETURN field of the revision (revocation) transaction, with the revision (revocation) address as one of its outputs. The concept of a local credential id has been introduced to allow a revision (revocation) list to be efficiently stored on a blockchain system. It is based entirely on a blockchain system and does not require any centralized authority. It is also applicable to most blockchain systems. A comparative study of the proposed method against existing credential revocation methods is also provided.
Keywords: blockchain in education; credential revision; credential revocation; learning credential